Identificação de incompatibilidade legal na área especial de conservação natural do Aquífero Arenito Basal Santa Maria, Santa Maria/RS - Follmann, Fernanda Maria (2012)
Currently with the increase of demand for water, we find that groundwater has, in most aquifers, the desired quality for domestic, industrial and agricultural supply. Thus, the most effective way to protect this water sources of possible pollution and guarantee quality recharge is by following the laws that deal with the protection of aquifer recharge areas, these must have restriction in soil use and occupation. We highlight the Special Area of Conservation of Natural Sandstone Aquifer Basal Santa Maria or Natural Conservation Area AC8, in Santa Maria, RS, as an area to be protected. Since according to the Law of Soil Use and Occupation of Santa Maria, the recharge area has to be protected from its possible pollution. Among the research aims are the estate and federal law verification regarding the protection of groundwater resources and, at the municipal level, what are the restrictions of soil use for the Natural Conservation Area AC8. The definition, identification and spatialization of potentially polluting soil uses and occupation in this area are also aims of this research, as well as generating a map of legal conflict of Natural Conservation Area AC8. For this, we obtained data from the network of sewage collection CORSAN and information about land ordering of the study area in Santa Maria's City Hall. As results we have the analysis of how the protection of groundwater resources occur in the law, the definition of potentially water polluting sources and the diagnose of areas with use of potentially water polluting in the recharge area of the Sandstone Aquifer Basal Santa Maria, for instance food and drink industries, concrete industries, metallurgical, gas stations, repair shops and lake of a network sewage collection. Through this law identification and analysis and implementation dates of activities of potentially polluting the recharge aquifer area, we determined the areas of legal conflict existent in the Natural Conservation Area AC8